2009
DOI: 10.1103/physrevlett.103.207403
|View full text |Cite
|
Sign up to set email alerts
|

Explanation of Photon Correlations in the Far-Off-Resonance Optical Emission from a Quantum-Dot–Cavity System

Abstract: In a coupled quantum-dot nano-cavity system, the photoluminescence from an off-resonance cavity mode exhibits strong quantum correlations with the quantum dot transitions, even though its autocorrelation function is classical. Using new pump-power dependent photon-correlation measurements, we demonstrate that this seemingly contradictory observation that has so far defied an explanation stems from cascaded cavity photon emission in transitions between excited multiexciton states. The mesoscopic nature of quant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
190
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(204 citation statements)
references
References 20 publications
11
190
2
Order By: Relevance
“…Importantly, we detect single-photon count rates of 460 kilocounts per second while maintaining a single-photon purity greater than 99%. This latter feature provides a significant advantage over cavity-based nanostructures where increased multiphoton events occur at saturation of the quantum dot emission due to cavity feeding of other quantum dots or detuned transitions of the same quantum dot [16,17]. Finally, by cooling the sample to 300 mK we show that the coherence can be enhanced by a factor of ∼2 as compared to operation at 4.5 K by further suppressing interactions with phonons.…”
Section: Introductionmentioning
confidence: 77%
“…Importantly, we detect single-photon count rates of 460 kilocounts per second while maintaining a single-photon purity greater than 99%. This latter feature provides a significant advantage over cavity-based nanostructures where increased multiphoton events occur at saturation of the quantum dot emission due to cavity feeding of other quantum dots or detuned transitions of the same quantum dot [16,17]. Finally, by cooling the sample to 300 mK we show that the coherence can be enhanced by a factor of ∼2 as compared to operation at 4.5 K by further suppressing interactions with phonons.…”
Section: Introductionmentioning
confidence: 77%
“…10 A number of surprises have emerged, distinguishing QD-based QED from its atomic counterpart, including the breakdown of the pointdipole description of light-matter interaction, 11 the role of phonon dephasing, [12][13][14] and multiple-charge transitions. 15,16 In this paper, we explore the role of environmental fluctuations by employing a QD embedded in a nanocavity as a sensitive probe of the phonon dephasing processes in a photoniccrystal (PC) nanomembrane. We compare our experimental data to a microscopic theory for longitudinal acoustic (LA) phonons and extract the effective phonon density of states (DOS) for the QD, which is the key concept describing all aspects of phonon dephasing.…”
Section: Introductionmentioning
confidence: 99%
“…After the preparation of this Rapid Communication, Winger et al 30 reported a theoretical model, which provides a quantitative description of the coupling of QD excitons to WL carriers. Our data provide a direct experimental confirmation of the main assumption in the model of Winger et al…”
mentioning
confidence: 99%